Focusing on the implementation of 21st century vaccines for adults. Issue 36 (28th August 2018) - Bonanni, Paolo; Bonaccorsi, Guglielmo; Lorini, Chiara; Santomauro, Francesca; Tiscione, Emilia; Boccalini, Sara; Bechini, Angela
Abstract: Adult immunization is a priority for public health, particularly in countries where an aging population has become increasingly more numerous. Protection against diseases which typically affect adults (like flu, pneumococcal diseases and Herpes zoster), the shift of age of infections which originally affected children (like measles), the decreasing protection with time for infections which need periodical booster doses of vaccines (Tdap), the availability of vaccines which can also impact on adult health (HPV) are only some examples of the importance of implementing targeted vaccination strategies. The possibility to reach high coverage with immunizations that can guarantee a fundamental improvement of health for adults and the elderly can only be achieved through a coordinated effort where all stakeholders, under the coordination of public health, contribute to issue recommendations; create a functioning database for vaccine coverage registration; promote formative courses for healthcare workers and continuous information for the public; increase vaccines uptake among healthcare workers, who need to give the first testimony on the relevance of immunization.